Accurate detection of SNPs using base-specific cleavage and mass spectrometry - Sun, Ruimin (2013)
Accurate detection of single-nucleotide polymorphisms (SNPs) is crucial for the success of many downstream analyses such as clinical diagnosis, virus identification, genetic mapping and association studies. Among many others, one valuable approach for SNP detection is based on the base-specific cleavage of single-stranded nucleic acids followed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) analysis. In this paper, we present a new SNP detection algorithm, which in particular permits an efficient and effective integration of the information in four complementary base-specific mass spectra. The new algorithm was implemented in a program called SnpMs. Comparative evaluation has been carried out on both simulated and real biological datasets, where experimental results clearly demonstrated the high ability of SnpMs as a tool to accurately detect SNPs.